The influence of curriculum strengthening and implementation of islamic religious education textbooks on student academic achievement at Darusalam Islamic Boarding School Mojogedang in the academic year 2024/2025 - Ahmad Suparno Basri; Siti Rohimah (At Turots: Jurnal Pendidikan Islam, 2025)
This study is motivated by the importance of curriculum strengthening and the effectiveness of Islamic Religious Education (IRE) textbook implementation in enhancing student academic achievement at Islamic boarding schools. In the context of Islamic value-based education, the role of curriculum and instructional materials becomes a strategic component in promoting optimal learning outcomes. This research aims to analyze the influence of curriculum strengthening and IRE textbook implementation on the academic achievement of students at Darusalam Islamic Boarding School Mojogedang in the Academic Year 2024/2025. The methodology employed is a quantitative approach with associative research design. The research population consists of 30 seventh-grade students who were selected as the total sample. The instruments used were questionnaires and documentation of academic scores, analyzed using multiple linear regression with SPSS version 26. The results demonstrate that both curriculum strengthening and textbook implementation have significant partial and simultaneous effects on student academic achievement. The coefficient of determination (R²) of 32.3% indicates the contribution of both independent variables to the dependent variable. The implications of this research underscore the importance of contextual curriculum design and adaptive instructional material usage as strategies for improving the quality of IRE learning in Islamic boarding school environments. This study recommends continuous curriculum development and teacher training.